PENGARUH KOMPRES HANGAT JAHE EMPRIT TERHADAP PENURUNAN NYERI SENDI LUTUT ARTHRITIS REMATHOID PADA LANSIA DI PANTI SOSIAL TRESNA WERDHA (PSTW) BONDOWOSO - Muhammad Ali; Gumiarti; Mahmud Ady Yuwanto (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
Arthritis Rheumatoid is one of an autoimmune disease in which the joints are usually the hands and feet joints going inflammation resulting in swelling, Pain and often finally causing damage to the inside of the joint. Pain management in the elderly aims to reduce pain or eliminating the pain of the knee atritisremathoid joints in the elderly. The purpose of this research is to determine the effect of warm compresses of ginger emprit on decreasing scale of knee joint pain in rheumatoid arthritis in elderly. This type of this research is pre experiment with one group design pre-post test design. The population of this research is elderly who live in Bondowoso old age social services and have certain characteristics. The sample amounted to 20 elderly people with total sampling technique. The result of the research before the giving of warm compress ginger emprit showed that the elderly suffer on medium pain scale that is 70,0%. Pain scale after done giving warm compress ginger emprit, knee joint pain in elderly decreased with mild pain scale that is 75,0%.Based on Wilcoxon statistic test obtained calculation p-value 0,00 (<0,05). So it shows there is a significant influence between the influence of warm compresses of ginger emprit on the decrease the scaleof knee rheumatoid arthritis joints pain in elderly. It is advised to the elderly that warm compresses of ginger emprit can be used as an independent intervention to decreasethe scale of knee rheumatoid arthritis joint paint